Facing society's demands for environmental protection: Management in practice - Pizzolatto, Allayne Barrilleaux (Journal of business ethics, 1993)
Although managers must stay abreast of all socictal concerns in developing organizational objectives, protecting the environment seems to be a major issue for consumers in the 1990s. This increased environmental concern leaves managers no choice but to go beyond mere social obligation when it comes to protecting the environment. Society is demanding social responsiveness at a minimum, and the call for social responsibility seems to be getting louder and clearer. This paper reviews the response business has made to this call for responsibility for the environment. Specifically, this paper will address the impact of increased business awareness on: (1) the passage of laws and legislation to protect the environment (social obligation); (2) specific organization actions to meet consumer demands (social responsiveness); (3) specific organization endeavors which reflect a sincere attempt to address the environmental issue (social responsibility). An awareness of these activities should aid managers in developing future plans which will allow them to become more responsible for our environment.